Aging Induces Changes in the Somatic Nerve and Postsynaptic Component without Any Alterations in Skeletal Muscles Morphology and Capacity to Carry Load of Wistar Rats - Krause Neto, Walter; Silva, Wellington de Assis; Ciena, Adriano P.; de Souza, Romeu R.; Anaruma, Carlos A.; Gama, Eliane F. (Frontiers in Neuroscience, 2017)
This study aimed to analyze the effects of aging on the components of the neuromuscular system (peripheral nerve, end-plate, skeletal muscle and weigth-bearing capacity) of Wistar rats. Twenty rats were divided into groups: 10 months old (ADULT) and 24 months old (OLD). After euthanasia, we prepared and analyzed the tibial nerve using transmission electron microscopy and the soleus and plantaris muscles for cytofluorescence and histochemistry. For the tibial nerve, the OLD group presented the following alterations compared to the ADULT group: larger area and diameter of both myelinated fibers and axons, smaller area occupied by myelinated and unmyelinated axons, lower numerical density of myelinated fibers, and fewer myelinated fibers with normal morphology. Both soleus and plantaris end-plate showed greater total perimeter, stained perimeter, total area and stained area in the OLD group compared to ADULT (p<0.05). The soleus end-plate showed greater dispersion in the OLD group (p<0.05). For the morphology of soleus and plantaris, the density of the interstitial volume increased in the OLD group (p<0.05). No statistical difference was found between groups in the carried load tests. The results of the present study demonstrated that the aging process induces changes in the peripheral nerve and motor end-plate without any change in skeletal muscles and ability to carry load in rats.